Impact of antibiotics on smell dysfunction. Issue 1 (1st March 2018) - Wang, Jing‐Jie; Chen, Jonathan; Doty, Richard L.
Abstract : Objective: Viral or bacterial respiratory infections can cause long‐lasting olfactory dysfunction. Antibiotic therapy is indicated in severe cases; however, it is unclear whether antibiotic use produces a positive, negative, or null effect on olfactory function. This retrospective study sought to determine whether antibiotic use has an influence on odor identification and detection threshold test scores of patients with smell dysfunction secondary to upper respiratory infections (URIs), lower respiratory infections (LRIs), or rhinosinusitis. Methods: Data from a total of 288 patients presenting to the University of Pennsylvania Smell and Taste Center were evaluated. Results: Patients with a URI etiology who had taken bactericidal antibiotics had lower detection thresholds than did patients who had not taken antibiotics ( P < 0.023; analysis of covariance with age and time since infection onset as covariates). Moreover, thresholds were lower for bactericidal antibiotic users than for bacteriostatic antibiotic users with either URI ( P = 0.023) or rhinosinusitis ( P = 0.028) etiologies. No meaningful influences of antibiotics on the odor identification test scores were evident. Conclusions: These findings, which need to be confirmed in prospective double‐blind studies, suggest that bactericidal antibiotic therapy may be beneficial in mitigating, at least to some degree, chronic decrements in smell sensitivity due to URIs and rhinosinusitis.